Progression of sacroiliitis in men and women according to the cohort of early axial spondyloarthritis (CORSAR) over 3 years of follow-up - D. G. Timokhina; T. V. Dubinina; A. B. Demina; O. A. Krichevskaya; Sh. F. Erdes (Научно-практическая ревматология)
Axial spondyloarthritis (axSpA) is a chronic inflammatory disease with predominant involvement of the sacroiliac joints (SIJ) and/or the spine. Despite the fact that the prevalence of axSpA is almost the same in men and women, there is evidence of a delay in diagnosis and a more severe course of the disease in females. The available reports on the progression of structural changes in the SIJ in men and women with early axSpA are contradictory. Meanwhile, the analysis of radiographic progression in the SIJ has fundamental importance both for timely diagnosis and for assessing the effectiveness of therapy in axSpA. Such studies have not yet been carried out in the Russian Federation.Objective: to assess the radiographic progression of sacroiliitis (SI) over 3 years in men and women with early axSpA.Material and methods. The study included patients from the cohort of early axSpA CORSAR, formed at the V.A. Nasonova Research Institute of Rheumatology. Currently, it includes 175 patients with axSpA. We analyzed the data of 64 patients, followed for at least 3 years. To assess the radiographic progression of the disease at baseline and after 3 years, the sum of X-ray stages of SI in the left and right SIJ was determined (the total stage of SI). Progression was assessed by the change in the total stage of SI in the right and left SIJ (0-8) during the observation period. We also calculated the proportion of patients with deterioration (increase in the total stage of SI by at least 1 stage), with improvement (decrease in the total stage of SI by at least 1 stage) and without progression. In order to fully exclude the error in measuring the radiographic progression of SI, we counted patients with “net” progression, that is, the proportion of patients with improvement was subtracted from the proportion of patients with deterioration.Results. Among 64 patients with early axSpA, there were 37 (57.8%) men and 27 (42.2%) women. For 3 years, the median of the total stage SI in men was 0 [0; 1], in women - 0 [0; 2] (p>0.05). When assessing the progression of the total stage SI over 3 years, no significant differences were found between the number of men and women with improvement, with deterioration, “net” progression and without progression. Men with early axSpA showed a higher level of C-reactive protein (CRP) at baseline, women had higher BASDAI and ASDAS CRP values after 3 years. In 8% of patients, there was a regression of X-ray signs of SI.Conclusion. The radiographic progression of SI in patients with early axSpA does not depend on gender and disease activity. In some patients with early axSpA, reverse development of structural damage to the SIJ is possible.